Development of pediatric neurosurgery in India - Bhagwati, S. N. (Medknow Publications, 2011)
The development of pediatric neurosurgery in this country actually began with holding of the 17(th) Annual Conference of the International Society for Pediatric Neurosurgery (ISPN) in 1989 in Mumbai. It subsequently led to the formation in 1990 of the Indian Society for Pediatric Neurosurgery (IndSPN), which is responsible for organizing regular annual conferences and CMEs in cooperation with the ISPN. The first three international CME programs were arranged in 1992, 1994 and 1995, followed by the next three courses from 1998 to 2000. Subsequently, five more such programs were organized in 2002, 2004, 2007, 2009, and 2010. The official publication, Journal of Pediatric Neurosciences (JPN), which was started in 2006, has also made good progress in the last 5 years. In the last 20 years, the IndSPN has made striking progress in the development and growth of pediatric neurosurgery in the country and has successfully managed to bring this subspeciality to an international level. The IndSPN now has about 150 active members and quite a few of them practice mainly pediatric neurosurgery. In large teaching institutions, pediatric neurosurgery has been accepted as a subspeciality with a designated neurosurgeon taking care of the pediatric patients. This augers well for the subspeciality as persons with greater interest and expertise will be tackling its problems. Some of these institutions have recently started or are in the process of starting the 1-year fellowship training program in pediatric neurosurgery.